2014
DOI: 10.1111/ijn.12311
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between characteristics of nursing performance and years of experience in nurses with high emotional intelligence

Abstract: The aim of this study was to elucidate characteristics of nursing performance among nurses with high emotional intelligence (EI) and examine the influence of years of experience on nursing performance and EI. A survey, including The Emotional Intelligence Scale and the Six-Dimension Scale of Nursing Performance, was administered to 1395 nurses working at general hospitals in Japan from November 2010 to March 2011. We received 1045 responses (76% response rate). There was a significant positive correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 13 publications
4
34
1
3
Order By: Relevance
“…These results are congruent with previous findings that higher EI is associated with better mental health (Görgens-Ekermans and Brand, 2012;Martins et al, 2010;Mikolajczak et al, 2007;Santos et al, 2015), higher work engagement (Nel et al, 2014;Zhu et al, 2015) and better job performance (Fujino et al, 2015;O' Boyle et al, 2011).…”
Section: The Beneficial Profiles Of Eisupporting
confidence: 91%
See 2 more Smart Citations
“…These results are congruent with previous findings that higher EI is associated with better mental health (Görgens-Ekermans and Brand, 2012;Martins et al, 2010;Mikolajczak et al, 2007;Santos et al, 2015), higher work engagement (Nel et al, 2014;Zhu et al, 2015) and better job performance (Fujino et al, 2015;O' Boyle et al, 2011).…”
Section: The Beneficial Profiles Of Eisupporting
confidence: 91%
“…Hypothesis 5 (H5): EI profiles with higher interpersonal EI compared with other EI dimensions within the profile will also be associated with poorer outcomes (Fujino et al, 2015;Gerits et al, 2005).…”
Section: Hypothesis 3 (H3): Ei Profiles With Lower Interpersonal Ei Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Odnotowano wysoki poziom dodatniej korelacji pomię-dzy poziomem inteligencji emocjonalnej, a rozwojem zawodowym pielęgniarek. Zaobserwowano także, że im dłuższy staż pracy w zawodzie, tym wyższy poziom wydajności pracy [31].…”
Section: Przegląd Badań Nad Wydajnością Pracy Pielęgniarekunclassified
“…They also promote their own learning and nursing skills (14). The results of different studies showed a positive correlation between nurses' EI and JS (15,16).…”
Section: Introductionmentioning
confidence: 98%